1997
DOI: 10.1073/pnas.94.14.7406
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a gene (RIG-G) associated with retinoic acid-induced differentiation of acute promyelocytic leukemia cells and representing a new member of a family of interferon-stimulated genes

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 31 publications
2
62
0
1
Order By: Relevance
“…For a long time this family genes have been identified just in mammals, including human IFI60, IFI58, IFI56, IFI54, hamster IFI54, mouse homologues GARG-16, GARG-39 and GARG49/IRG2, and rat homologues GARG-16 (Levy et al, 1986;Lee et al, 1994;Smith and Herschmann, 1996;Niikura et al, 1997;Yu et al, 1996;de Veer et al, 1998, Kitamura et al, 2001. TPR motifs are characterized as 34 loosely conserved residues that are classified into two subdomains containing the hydrophobic residues particularly conserved at the consensus sites 4-7-8-11 and 20-24-27-32 (Smith and Herschmann, 1996;Das et al, 1998), and may be dispersed throughout the protein sequence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For a long time this family genes have been identified just in mammals, including human IFI60, IFI58, IFI56, IFI54, hamster IFI54, mouse homologues GARG-16, GARG-39 and GARG49/IRG2, and rat homologues GARG-16 (Levy et al, 1986;Lee et al, 1994;Smith and Herschmann, 1996;Niikura et al, 1997;Yu et al, 1996;de Veer et al, 1998, Kitamura et al, 2001. TPR motifs are characterized as 34 loosely conserved residues that are classified into two subdomains containing the hydrophobic residues particularly conserved at the consensus sites 4-7-8-11 and 20-24-27-32 (Smith and Herschmann, 1996;Das et al, 1998), and may be dispersed throughout the protein sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the genomic structure for human IFI60, IFI54 and IFI56, mouse IFI54 and IFI56, hamster IFI54 showed that they are all composed of a small first exon and the second exon that contains all ORF except the ATG start codon and two nucleotides of the second codon (Levy et al, 1986, Wathelet et al, 1988Bluyssen et al, 1994;Yu et al, 1996, de Veer et al, 1998). In the current study, both IFIT family members are identified in crucian carp, and one pufferfish member has been found by search of pufferfish genome database, demonstrating that IFIT family genes exist in fish, too.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR-based differential display of cDNA 38 is a powerful approach to identify novel genes that are directly or indirectly regulated after RA stimulation. Using this method, several novel genes have been identified during NB4 cell maturation, including RIG-E, 42 RIG-G 43 and JEM-1. 44 It will be important to characterize the common denominator in the expression of these genes: are they a direct target of RA or controlled by distinct signalling?…”
Section: Introductionmentioning
confidence: 99%